Efectividad agronómica y económica de fertilizantes compuestos en cacao CCN-51 en Chone Manabí - Flecher Ponce, Esperanza Magdalena (2022)
According this researching project, evaluating the agronomic and economic effectiveness was the main goal of compound fertilizers in CCN-51 cocoa in Chone, Manabí. On the other hand, the treatments consisted on five fertilizers sources (Ferticacao Plus, Ecocacao Plus, Seos Cacao, Integrative Yaramilla and Novatec Premium) and three fertilization doses (400, 800 and 1200 g/plant). As a result; 16 treatments, three repetitions and 48 experimental units were evaluated. In addition, the main variables evaluated were healthy ears, dry grain yield and net economic benefit of fertilization. So that, the results showed statistically significant differences (p<0.05) for the main effects sources and dose, but not for the interaction sources x dose (p>0.05). The mixture chemical sources (Yaramilla Integrative) and slow release (Novatec Premium), regardless of the dose, achieved the highest production of healthy ears, dry grain yield and net economic benefit. In summary, the dose of 1200 g/plant achieved the highest grain yield, regardless of the sources tested. From the economic point of view, we obtained a great difference with the Integrative Yaramilla and Novatec Premium fertilizers applied at doses of 800 g/plant, these were the best economic alternatives for the fertilization and dosage of CCN-51 cocoa under the conditions of the Chone canton. where the research was carried out